2000
DOI: 10.1046/j.1365-2672.2000.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of propolis against Streptococcus pyogenes

Abstract: Propolis, a multifunctional substance used by bees to maintain the safety of their hives, is popular for its therapeutic potential against some micro‐organisms. Ethanolic extracts of two propolis specimens, collected from different areas within a region in the north‐west of Italy, were examined to evaluate their antimicrobial activity against 46 Streptococcus pyogenes strains. By both agar dilution and agar diffusion methods, the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 16 publications
(25 reference statements)
0
94
0
14
Order By: Relevance
“…Propolis has been shown to kill Bacillus larvae, the most important bacterial disease of bees (20). Flavonoids such as Chrysin and Quercetin account for much of the biological activity in propolis.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has been shown to kill Bacillus larvae, the most important bacterial disease of bees (20). Flavonoids such as Chrysin and Quercetin account for much of the biological activity in propolis.…”
Section: Discussionmentioning
confidence: 99%
“…This test was apparently not influenced by the solubility of the active components in the broth. Using serial dilution in tubes for European propolis, MBC of 1.5 mg/ mL for S. aureus (14) and of 3.0 mg/mL for S. aureus and S. epidermidis (8) Bosio et al (4) used both dilution and diffusion methods to study the activity of Italian propolis against S. pyogenes concluding that, whereas the results of the agar diffusion tests with disks were not suitable for comparing specimens, the agar dilution tests gave results that corresponded to the results of the HPLC tests.…”
Section: Discussionmentioning
confidence: 99%
“…Owing the ability to synthesize many different substances, the propolis is one of the top richest sources of new drugs (1,11). It is showed that ethanol extract of propolis has a high potential as an alternative source of antibacterial compounds (2,3,4,5,13,19,20,22,33).…”
Section: Introductionmentioning
confidence: 99%